Peningkatan Efektivitas Mesin Gluer JK-1000 Melalui Pendekatan Overall Equipment Effectiveness (OEE) dan Reliability Centered Maintenance (RCM) pada Industri Packaging - Aldo Fadra Witanto; Siti Muhimatul Khoiroh (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT XYZ is a packaging printing company whose production process highly depends on machine performance. One of the critical machines is the Gluer JK-1000, which is used in the folding and gluing stages of packaging production. This study aims to evaluate the effectiveness of the Gluer JK-1000 machine using the Overall Equipment Effectiveness (OEE) method and to determine an appropriate maintenance strategy through the Reliability Centered Maintenance (RCM) approach. The study utilized operational and production data collected from August to December 2025. The results showed that the Availability Rate, Performance Rate, and Quality Rate were 90.97%, 89.10%, and 87.40%, respectively, resulting in an OEE value of 70.84%, which is below the 85% standard established by the Japan Institute of Plant Maintenance (JIPM). Six Big Losses analysis revealed that Reduced Speed Losses and Setup and Adjustment Losses were the dominant sources of productivity loss, contributing 15.47% and 8.11%, respectively, with a cumulative contribution of 81.95%. FMEA identified critical components consisting of the Feeding Belt (RPN 252), Sensor Gluing (RPN 245), Roller Gluer (RPN 224), and Side Lay Register (RPN 210). Based on the RCM analysis, maintenance recommendations were developed through Time Directed Maintenance and Condition Directed Maintenance approaches, with preventive maintenance intervals determined according to component reliability analysis. The findings can be used as a basis for improving machine reliability and reducing downtime risk in the production process.